2017
DOI: 10.1080/10810730.2016.1266715
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Health Reporting Knowledge and News Gathering Practices of Health Journalists and Editors at Community Newspapers

Abstract: This research adds to our understanding of health and science reporting by identifying and examining the numbers, types, and simultaneous uses of resources selected by health and science journalists and editors at the initial stages of reporting, and relates this to journalists' perceived health reporting knowledge. A telephone survey of 141 health and science journalists and editors selected from 259 community newspapers in Missouri was conducted. Information sources included those that were highly credible, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Whereas, the studies found from non-Western states focus on 'individual social or political issues such as corruption in India (Rodrigues, 2014). With this increase in terms of popularity (Saldaña et al, 2017), social media has become a powerful tool for journalists and news organisations ranging from health journalism (Shoenberger, Rodgers, 2017) to sports journalism (Li et al, 2017), including emergency journalism (Bowdon, 2014) and political journalism (Parmelee, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, the studies found from non-Western states focus on 'individual social or political issues such as corruption in India (Rodrigues, 2014). With this increase in terms of popularity (Saldaña et al, 2017), social media has become a powerful tool for journalists and news organisations ranging from health journalism (Shoenberger, Rodgers, 2017) to sports journalism (Li et al, 2017), including emergency journalism (Bowdon, 2014) and political journalism (Parmelee, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They also discovered government websites and nonprofit websites are useful for providing background information (Viswanath et al, 2008). Shoenberger and Rodgers (2017) also conducted surveys of over 250 health and science journalists and editors from community newspapers in the state of Missouri and found government and nonprofit websites are reliable information resources at the initial stage of reporting. Health and science journalists value websites that are convenient to access for their ability to save time when working under tight deadlines (Shoenberger and Rodgers, 2017; Viswanath et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shoenberger and Rodgers (2017) also conducted surveys of over 250 health and science journalists and editors from community newspapers in the state of Missouri and found government and nonprofit websites are reliable information resources at the initial stage of reporting. Health and science journalists value websites that are convenient to access for their ability to save time when working under tight deadlines (Shoenberger and Rodgers, 2017; Viswanath et al, 2008). The Internet is heavily used by science journalists, with the top activities being researching articles and reference materials and reading publications (Grando, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With this increase in terms of popularity [30], social media has become a powerful tool for journalists and news organisations ranging from health journalism [31] to sports journalism [32], including emergency journalism [33] and political journalism [34]. Social media in the context of journalism is being mainly used in the following three ways: (i) as a venue to freely post news stories to reach out to potential new readers and increase the number of visitors on their websites, cf.…”
Section: Social Media For Journalistsmentioning
confidence: 99%